Пержанські граніти — новий тип рідкіснометалевих апогранітів - Романюк, Л.С. (Інститут геологічних наук НАН України, 2009)
Приведена характеристика пержанских гранитов как нового типа редкометальных образований — сидерофиллит-калишпат-пертитовых апогранитов. Их происхождение связано с развитием площадных метасоматических преобразований в границах Сущано-Пержанской зоны тектоно-магматической активизации в северо-западной краевой части Украинского щита. С этими гранитами связано продуктивное редкометальное оруденение бериллия, ниобия, тантала, олова, вольфрама, циркония, лития и других металлов. The characteristic of Perha granites as new type of rare metals formations — syderophyllite-potassic feldspar-perthite apogranites is given. Their genesis is connected with development of areal metasomatic transformation within the limits of Sushchany-Perha zone of tectonic-magmatic activation in the north-western periphery part of the Ukrainian Shield. The productive rare metals mineralization of beryllium, niobium, tantalum, tin, tungsten, zirconium, lithium and other metals is connected with these granites.